2014
DOI: 10.3389/fnhum.2014.00093
|View full text |Cite
|
Sign up to set email alerts
|

It's how you get there: walking down a virtual alley activates premotor and parietal areas

Abstract: Voluntary drive is crucial for motor learning, therefore we are interested in the role that motor planning plays in gait movements. In this study we examined the impact of an interactive Virtual Environment (VE) feedback task on the EEG patterns during robot assisted walking. We compared walking in the VE modality to two control conditions: walking with a visual attention paradigm, in which visual stimuli were unrelated to the motor task; and walking with mirror feedback, in which participants observed their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
170
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(197 citation statements)
references
References 93 publications
26
170
1
Order By: Relevance
“…In accordance with different studies ( [14,[62][63][64][65] the analysis of the event related spectral perturbation (ERSP) during walking shows specific power increases (interpreted as an event related synchronization, ERS) or decreases (even related desynchronization, ERD). Figure 1 illustrates such type of results recorded from C3 and C4 electrodes which are anatomically placed over the left and right sensorimotor areas corresponding to the left and right hand region, respectively, during 50 walking cycles.…”
Section: Eeg During Walking Executionsupporting
confidence: 72%
See 1 more Smart Citation
“…In accordance with different studies ( [14,[62][63][64][65] the analysis of the event related spectral perturbation (ERSP) during walking shows specific power increases (interpreted as an event related synchronization, ERS) or decreases (even related desynchronization, ERD). Figure 1 illustrates such type of results recorded from C3 and C4 electrodes which are anatomically placed over the left and right sensorimotor areas corresponding to the left and right hand region, respectively, during 50 walking cycles.…”
Section: Eeg During Walking Executionsupporting
confidence: 72%
“…This has resulted in much convergence in results but also some divergent evidence within this literature. Neurophysiological, neuroimaging and behavioral data have demonstrated a high sensitivity to kinematics of human movement [120,121] including walking [122,123] as in a selfimage mirror walking or virtual environment [63], reference frame [122,[124][125][126]. It is well known that shape and motion information are treated separately by ventral and dorsal visual streams, and converge to the posterior portion of superior temporal sulcus [111,127,128].…”
Section: Walking Observation and The Mirror Neuron Systemmentioning
confidence: 99%
“…Furthermore, a recent study using resting state functional magnetic resonance imaging found significant changes in activity in sensorimotor areas in a group of young individuals after 20 min of aerobic exercise (Rajab et al, 2014), while a couple of studies demonstrated that functional brain activity in motor areas increased proportional to the movement rate on a pedaling task executed during scanning (Mehta et al, 2012). Finally, increased SMA activation was observed during motor imagery of locomotor-related tasks (Malouin et al, 2003) as well as during real locomotion as measured by electrophysiological studies showing SMA modulation during walking (Petersen et al, 2012; Wagner et al, 2012, 2014; Seeber et al, 2015). Thus despite the scarcity of studies assessing cerebral structural and functional changes in relation to gait parameters and aerobic training in humans, the above mentioned studies provide basic evidence that AET can have a direct impact on the brain.…”
Section: Discussionmentioning
confidence: 95%
“…However, recent functional neuroimaging studies in humans have shown that the midline (i.e., the most medial) primary sensorimotor cortex is significantly active during steady-state walking (Fukuyama et al, 1997; Hanakawa et al, 1999; Miyai et al, 2001; Wagner et al, 2012, 2014; Seeber et al, 2014, 2015; Storzer et al, 2016). Specifically, within the gait cycle, the midline primary sensorimotor cortex cyclically increases its activity approximately between mid-beta and low-gamma frequencies (Wagner et al, 2012, 2014; Seeber et al, 2014, 2015; Storzer et al, 2016). Furthermore, Petersen et al (2012) have reported that, during treadmill walking, the activities of the midline primary motor cortex and the foot dorsiflexor become cyclically coherent, with similar timing and frequency range as the aforementioned increase in the midline sensorimotor activity.…”
Section: Introductionmentioning
confidence: 99%